2017
DOI: 10.2217/fmb-2016-0127
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Microbiome, PA Biofilm-Forming Capacity and Exacerbation in Severe COPD Patients Colonized by P. Aeruginosa

Abstract: The bronchial microbiome shows differences according with P. aeruginosa biofilm-forming capacity. Pathogenic microorganisms other than P. aeruginosa cause a significant part of the exacerbations in colonized chronic obstructive pulmonary disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 50 publications
0
19
0
3
Order By: Relevance
“…Wu et al showed a significant increase in abundance of Streptococcus pneumoniae, Klebsiella pneumoniae , and Pseudomonas aeruginosa in COPD as compared to healthy ( 51 ). Recently, this was further confirmed by Garcia-Nuñez et al that potentially pathogenic microorganisms other than P. aeruginosa can be the cause of exacerbations in COPD, and hence antibiotic treatments against the activity of other pathogens need to be considered while treating COPD ( 52 ).…”
Section: Microbiome In Copdmentioning
confidence: 84%
“…Wu et al showed a significant increase in abundance of Streptococcus pneumoniae, Klebsiella pneumoniae , and Pseudomonas aeruginosa in COPD as compared to healthy ( 51 ). Recently, this was further confirmed by Garcia-Nuñez et al that potentially pathogenic microorganisms other than P. aeruginosa can be the cause of exacerbations in COPD, and hence antibiotic treatments against the activity of other pathogens need to be considered while treating COPD ( 52 ).…”
Section: Microbiome In Copdmentioning
confidence: 84%
“…Thus, the examination of the respiratory microbiome confirms that a causal bacterial pathogen may keep unnoticed by conventional microbiology in some exacerbations, while the culture identifies microorganisms that are only colonizers. This equivocal information of conventional microbiology has been reported in up to twenty percent of patients chronically colonized by Pseudomonas aeruginosa (4,27).…”
Section: Exacerbationmentioning
confidence: 99%
“…An OTU will be considered to be equivalent to this reference at gender level when the sequence is at least 94% coincident, and to species when this coincidence is over 97%. The composition of the microbiome is in most cases expressed as relative abundance, meaning the proportion of copies of the 16S rRNA gene corresponding to each identified OTU from the whole, a value that has shown to be correlated with absolute microbial counts recovered at culture, at least for Pseudomonas aeruginosa (4). 16S rRNA gene analysis is unable to obtain virus and fungal information, however, and these microorganisms need to be targeted with other sequencing approaches.…”
Section: The Respiratory Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Узагальнення наукових публікацій останніх років показує, що перебування мікроорганізмів у дихальних шляхах є складовою патогенезу ХОЗЛ і, навіть, поза стадії загострення, вони приймають участь у прогресуванні ХОЗЛ, в більшості випадків, через активацію ефекторних клітин запалення [15,16,19,20,23,24].…”
unclassified